Blue mold control and volatile compounds in “Fuji” apples treated with chitosan emulsion combined with essential oils - Heinzen A.S.* (2022)
© 2022 Wiley Periodicals LLC.The aim of this work was to evaluate the effects of chitosan emulsion (CE) in combination with essential oils (Eos) on blue mold control, as well as on aroma and quality attributes of “Fuji” apples after storage. Treatments evaluated were control, CE (1%) and CE (1%) combined with citronella, clove and copaiba EOs (all EOs at 500 μl L−1). Fruits treated with EC and EC + OEs showed lower total phenolic compounds in the peel in all treatments. Fruits treated with EC combined with citronella OEs (242.4 OD mg–1 of protein min–1) and clove (205.8 OD mg–1 of protein min–1) showed lower peroxidase activity in fruit peel tissue. Therefore, CE and CE combined with citronella, clove and copaiba essential oils reduced the development of blue mold in “Fuji” apples. In addition, the treatments with lower severity of blue mold showed lower peroxidase activity in the peel and pulp tissues of the fruit, indicating induction of resistance by essential oils. Novelty impact statement: Chitosan biofilm reduces rot by P. expansum in “Fuji” apples, and when in addition to chitosan, essential oils of citronella, clove and copaiba are used, there was an increase in the reduction of disease severity. The aroma of the fruit did not present a characteristic aroma of the essential oils used with the method of application used. There were no changes in fruit quality attributes with the use of chitosan and chitosan biofilm with the addition of essential oils.